(untitled) (Profetik: Jurnal Komunikasi, 2021)
The political turmoil in Malaysia following the resignation of Mahathir Mohammad (February 2020), and the success of Muhyiddin Yassin in the position of Prime Minister, made the political atmosphere even more dynamic. There are those who think that Malaysian politics currently shows a serious problem with the fierce battle between political figures. There have even been various accusations that say there is treason that justifies any means to achieve the goal. Muhyiddin Yassin, who is Mahathir’s representative in the Malaysian Indigenous United Party (PPBM), was accused of treason. Likewise, Azmin Ali who was deputy chairman of the People’s Justice Party (PKR) was accused of treason by Anwar Ibrahim, so that Azmin was fired from the PKR. Mahathir Mohammad is a senior Malaysian political figure with long experience in politics. The political communication that Mahthir has built is very intelligent with his success as a UMNO figure and the Prime Minister of Malaysia for more than 20 years. As a doctor, since the age of 25, he has been active in politics through the UMNO party. Mahathir understands that politics is very dynamic and political figures must be able to adapt to the existing political dynamics. It was this political dynamic that made Mahathir leave UMNO when he saw the many deviations committed by his figures. Mahathir then formed a new party, Partai Pribumi Bersatu Malaysia (PPBM) which succeeded in ending UMNO’s domination in the 2018 elections. Mahathir’s political communications were truly tested when he succeeded in becoming the second prime minister of Malaysia at the age of 92 years. The political message delivered by Mahathir was able to convince the Malaysian people about the direction of national development. His long and successful experience in politics made him known as the father of modernization in Malaysia. However, in the end, he was removed by Muhyiddin Yassin (his own friend) from the seat of Prime Minister at the age of 94. Because actually in politics there are no friends and enemies who are eternal, it is political interests themselves that are eternal.